Efeitos da administração de estradiol e progesterona sobre a concentração hormonal e expressão endometrial dos receptores de estrógeno e progesterona em éguas receptoras acíclicas - Silva, Elisa Sant'Anna Monteiro da [UNESP] (2015)
To investigate the effects of the administration of 2.5 mg of estradiol benzoate (EB) followed by 1500 mg of long acting progesterone (LA P4) on endometrial molecular dynamics, uterine morphological characteristics, as well as estrogen and progesterone plasma concentrations in non-cyclic recipient mares, we evaluated: protein expression and changes in relative abundance of transcripts for estrogen (ER) and progesterone receptors (PR) in the endometrium by RT-qPCR and immunohistochemistry; uterine morphological characteristics by ultrasonography and rectal palpation; and estrogen and progesterone plasma concentrations by radioimmunoassay. The administration of 2.5 mg, 5 mg or 10 mg of EB were effective at promoting maximum uterine edema 24 h after their injection. The dose of 2.5 mg of EB caused similar estradiol concentration peaks to those observed in mares treated with 5 mg or10 mg of EB and to those observed in cyclic mares, which was not followed by increased concentrations of estrogen conjugate as observed for the other doses. Moreover, P4 concentration was reduced 24 h after LA P4 administration when the dose of 10 mg of EB was injected. The administration of the hormonal protocols altered the relative abundance of transcripts for ERα, ERβ and PR in non-cyclic mares as observed in cyclic ones when late estrus and early diestrus were compared. In conclusion, the use of 2.5 mg of EB followed by 1500 mg of LA P4 causes similar uterine morphology changes, relative abundance of transcripts for ERα, ERβ and PR, and estrogen and progesterone circulating concentrations to those found in cyclic mares